2019
DOI: 10.3389/fnins.2019.00520
|View full text |Cite
|
Sign up to set email alerts
|

Amide Proton Transfer Contrast Distribution in Different Brain Regions in Young Healthy Subjects

Abstract: Objectives: To define normal signal intensity values of amide proton transfer-weighted (APTw) magnetic resonance (MR) imaging in different brain regions. Materials and Methods: Twenty healthy subjects (9 females, mean age 29 years, range 19-37 years) underwent MR imaging at 3 Tesla. 3D APTw (RF saturation B 1,rms = 2 µT, duration 2 s, 100% duty cycle) and 2D T2-weighted turbo spin echo (TSE) images were acquired. Postprocessing (image fusion, ROI measurements of APTw intensity values in 22 different brain regi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 42 publications
1
20
1
Order By: Relevance
“…content in the cytoplasm and the base-catalyzed exchange rate at physiological pH range (21). However, it should be acknowledged that the APTw signal may be contaminated by a variety of other technical factors (18,(29)(30)(31)(32)(33)(34). It is known that water longitudinal relaxation time (T 1 ) influences the APTw signal.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…content in the cytoplasm and the base-catalyzed exchange rate at physiological pH range (21). However, it should be acknowledged that the APTw signal may be contaminated by a variety of other technical factors (18,(29)(30)(31)(32)(33)(34). It is known that water longitudinal relaxation time (T 1 ) influences the APTw signal.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, semi-solid magnetization transfer (MT) and other nearby CEST and relayed nuclear Overhauser enhancement (rNOE) saturation transfer effects have been shown to affect the APTw signal. Lastly an imperfect distribution of the irradiation power across the brain can trigger B1 effects which may also impact APTw intensity values (34). It has been hypothesized that the increase in APTw signal intensity values in MSL in MS patients may be caused by changes in the intracellular amide proton content.…”
Section: Discussionmentioning
confidence: 99%
“…First, we hypothesized that this might be related to the size of the sample; our sample size was 74, compared with 20 for Sartoretti et al Second, the effect of age on the APTw value cannot be ignored (33). The subjects of our study were middle-aged and elderly healthy people, while the subjects of Sartoretti et al (26) were young healthy volunteers. However, recent studies have shown no significant correlation between APT signals and age in any brain regions (35).…”
Section: Discussionmentioning
confidence: 95%
“…16 slices with a slice thickness of 3.85 mm were acquired. The first slice was centered at the inferior border connecting the rostrum and the splenium of the corpus callosum 19 , 20 . Details on how APTw imaging contrast was generated can be found in the supplementary material .…”
Section: Methodsmentioning
confidence: 99%
“…Table 1 shows the sequence parameters for the APTw sequence. We used a clinically approved APTw sequence [18][19][20] acquired in transverse oblique orientation parallel to the intercommissural line. 16 slices with a slice thickness of 3.85 mm were acquired.…”
Section: Subjectsmentioning
confidence: 99%